2019
DOI: 10.4236/pp.2019.102008
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Ethnomedicinal, Pharmacological, Phytochemical and Pharmaceutical Profile of Lady’s Finger (<i>Abelmoschus esculentus</i> L.) Plant

Abstract: Abelmoschus is a genus of about fifteen species belongs to the family Malvaceae. The herb, popularly known as Lady's Finger or Okra (in English) is a nutritional source used for both medicinal and culinary purposes. The plant is widely distributed from Africa to Asia, Southern Europe, and America. This comprehensive account provides a botanical description of the plant, its phytochemical constituents and pharmacological activities focusing anti-diabetic, anti-oxidant, anti-adhesive, gastro-protective, hepatopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… Highly toxic LC 50 - 3.98 μg/ml acetone extract, 47.66 μg/ml methanol, 100 μg/ml ethyl acetate and 138 μg/ml water. Dikko et al (2016) ; Mshelia et al (2016) ; Maroyi (2017e) ; Chowdhury et al (2019) ; Yusuf et al (2020) Malvaceae Sida acuta Burm. f. Chest pains Antioxidant, antimicrobial, antibacterial, antimalarial, cardiovascular, antiulcer, antiviral, analgesic and anti-inflammatory, anticancer, antipyretic, hepatoprotective, hypoglycemic and insecticidal activities.…”
Section: Methodsmentioning
confidence: 99%
“… Highly toxic LC 50 - 3.98 μg/ml acetone extract, 47.66 μg/ml methanol, 100 μg/ml ethyl acetate and 138 μg/ml water. Dikko et al (2016) ; Mshelia et al (2016) ; Maroyi (2017e) ; Chowdhury et al (2019) ; Yusuf et al (2020) Malvaceae Sida acuta Burm. f. Chest pains Antioxidant, antimicrobial, antibacterial, antimalarial, cardiovascular, antiulcer, antiviral, analgesic and anti-inflammatory, anticancer, antipyretic, hepatoprotective, hypoglycemic and insecticidal activities.…”
Section: Methodsmentioning
confidence: 99%
“…Okra (Abelmoschus esculentus L. Moench) is an annual plant and is believed to originate near Ethiopia in Africa [7,8], which was used for both medicinal and culinary purposes. A variety of health functions of okra, such as reducing blood-sugar and fat [9,10], antifatigue [11], antioxidant capacity and reducing inflammatory response in ethanol-induced acute gastricmucosal injury and providing neuroprotection in neurodegeneration diseases such as Alzheimer's disease have been reported in recent years [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that okra extract possesses an in vitro non-enzymatic inhibitor of lipid peroxidation in liposome effects and that its peel and seed powder contain significant in vivo antioxidant properties in streptozotocin-induced diabetic rats ( Liao et al, 2012 ; Mihretu et al, 2014 ). Abelmoschus esculentus plays a vital role in the human diet and health ( Petropoulos et al, 2018 ), it is a powerhouse of valuable nutrients, such as carbohydrates, minerals, and vitamins ( Adelakun et al, 2009 ; Chowdhury et al, 2019 ). ( Husen et al, 2019 ) stated that Abelmoschus esculentus is used medicinally for plasma replacement or expanding blood volume, also, its soluble fiber in the form of gums and pectins lowers serum cholesterol and the risk of heart diseases ( Husen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%